Patient and public involvement and engagement to improve impact on antimicrobial resistance - Emily Scott-Dearing; Vanessa Carter; Michael Corley; Philip Mathew; Ara Darzi (Nature Communications)
A step change is required in citizen awareness of the global antimicrobial resistance (AMR) health crisis. But we must move beyond awareness-raising to action, directly engaging and involving patients and public in scoping, testing and scaling solutions to ensure their adoption and impact.